Design of Self-Tuning Regulator Adaptive Cascade Control for Power Factor Correction in Boost Rectifier - Chiyo Saito; Connor Davis (Advances in Engineering and Intelligence Systems)
The widespread use of electronic devices in various applications has led to increased harmonic distortion in power lines, resulting in a decreased power factor and reduced overall power quality. Voltage rectifiers connected to the line can be significant sources of this distortion. To mitigate these effects, it is crucial to enhance the power factor and minimize line current harmonics. This study employs a cascade-controlled boost converter for power factor correction, leveraging both voltage and current regulation. By integrating a self-tuning regulator (STR) adaptive controller with online identification within each control loop, this approach dynamically adjusts to fluctuations in current consumption over time. The proposed method effectively reduces Total Harmonic Distortion (THD) and improves power factor, contributing to more efficient and reliable power systems.